2019
DOI: 10.1051/matecconf/201926605010
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Labour Productivity in Construction Projects of Pakistan

Abstract: Construction projects are considered crucial in every developed and developing country from the perspective of economic and social development. Thus, it is mandatory to achieve successful completion of the project. Efficient production is one of the significant criteria in ensuring the success of projects. An efficient production, labour productivity is considered an important aspect. Labour productivity is affected by several factors which are essential to study for productivity improvements. Since in Pakista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…We found that, by collaborating with research institutions, suppliers, and organisations from other industries, firms in construction could nurture their employees' knowledge and competencies, which is a cure for low productivity (Rahman et al, 2019), but also cultivate the firm's own structural capital through industrial learning, for instance through the identification of replicable best practices and construction processes.…”
Section: Contribution To Practicementioning
confidence: 99%
See 1 more Smart Citation
“…We found that, by collaborating with research institutions, suppliers, and organisations from other industries, firms in construction could nurture their employees' knowledge and competencies, which is a cure for low productivity (Rahman et al, 2019), but also cultivate the firm's own structural capital through industrial learning, for instance through the identification of replicable best practices and construction processes.…”
Section: Contribution To Practicementioning
confidence: 99%
“…Particularly problematic is the low investment in staff training, a relatively old problem that is vastly unaddressed even nowadays. Low salaries lead to difficulties in having a stable and motivated working force, leading to a high turnover of workers even from abroad, unfamiliar with the context of the project (Abdel-Wahab and Vogl, 2011;Allen, 1985;Rahman et al, 2019;Teicholz et al, 2001;Zhi et al, 2003) (Blanco et al, 2016;Bryer et al, 2016;CIDB, 1992;Hays, 2018;McNally, 2018) Few ICT investments and ICT integration…”
Section: Inadequate Management Of Human Resourcesmentioning
confidence: 99%
“…Many studies have been carried out on labour productivity in different countries where researchers considered many factors in their research like 50 factors [11] in Malaysia, 45 factors [12] in Israel, 83 factors [13] in the United States of America, 45 factors [14] in Kuwait, 27 factors [15] in Egypt, 52 factors [16] in Yemen. Similarly, Rahman et al [17] in Pakistan identified 33 factors affecting the labour productivity. It was observed in the literature survey that many researchers have used the method of the relative importance index (RII) to identify the top factors affecting productivity.…”
Section: *Author For Correspondencementioning
confidence: 96%
“…In Pakistan, the road projects are mostly sponsored by the Government and it is a fact that payments are delayed because of lengthy processes in the Government Departments [31]. Labour productivity is the least explored area in the construction industry of Pakistan [39]. The poor quality of labour productivity in Pakistan is because one-third of the workforce is illiterate that make it difficult to learn new skills and master new technologies.…”
Section: Introductionmentioning
confidence: 99%